Quantifying environmentally relevant and circular plastic innovation Historical trends, current landscape and the role of policy - Dussaux, Damien (OECD Publishing, 2022)
Innovation is key to reducing the environmental impacts of plastics. However, literature is generally lacking in the field of environmentally relevant plastics innovation. This paper develops an innovative conceptual framework to document and map environmentally relevant plastics innovation. Using this framework, it develops plastics innovation metrics using patents and trademarks to quantify trends over time, across countries, and to establish preliminary empirical links between policies and innovation outcomes. Plastic waste prevention and recycling innovation has increased slightly more rapidly than overall plastics innovation. In contrast, innovation in bioplastics have witnessed a significant slowdown in recent years. Another key finding of this analysis is that environmentally relevant plastics innovation is concentrated in OECD countries and China and that top inventor countries are not specialized in the same technologies. Finally, the patent analysis shows some empirical evidence that recycling regulations may have triggered innovative activity in plastic recycling
Keywords: Environment